2022
DOI: 10.3390/md20020085
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Quorum-Sensing Activity of Tryptophan-Containing Cyclic Dipeptides

Abstract: Quorum sensing (QS) can regulate the pathogenicity of bacteria and the production of some virulence factors. It is a promising target for screening to find anti-virulence agents in the coming post-antibiotics era. Cyclo (L-Trp-L-Ser), one variety of cyclic dipeptides (CDPs), isolated from a marine bacterium Rheinheimera aquimaris, exhibited anti-QS activity against Chromobacterium violaceum CV026 and Pseudomonas aeruginosa PAO1. Unlike the CDPs composed of phenylalanine or tyrosine, the anti-QS activity has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…These compounds showed QS inhibition with IC 50 values of 26.8, 7.9, 30.7, and 56.2 μM, respectively (Figure S9). Interestingly, our findings suggest that pyrazines with a benzyl substitute have stronger inhibitory effects on QS than their previously reported analog cyclodipeptides (CDPs). Molecular docking (Figure S10) indicated that these compounds might compete with QS molecules for binding to the QS receptor CviR (PDB 3QP8), implying their potential to combat other strains that use N-Acyl homoserine lactone (AHL) as their signaling molecule, such as Vibrio and Pseudomonas . Given the protease inhibition potential demonstrated by amino acid–based N-heterocycles, including calpain inhibitors PZN-FV and PZN-YL, , as well as SARS-CoV-2 inhibitor PZ-WW, we next sought to investigate the protease inhibitory activities of isolated compounds.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…These compounds showed QS inhibition with IC 50 values of 26.8, 7.9, 30.7, and 56.2 μM, respectively (Figure S9). Interestingly, our findings suggest that pyrazines with a benzyl substitute have stronger inhibitory effects on QS than their previously reported analog cyclodipeptides (CDPs). Molecular docking (Figure S10) indicated that these compounds might compete with QS molecules for binding to the QS receptor CviR (PDB 3QP8), implying their potential to combat other strains that use N-Acyl homoserine lactone (AHL) as their signaling molecule, such as Vibrio and Pseudomonas . Given the protease inhibition potential demonstrated by amino acid–based N-heterocycles, including calpain inhibitors PZN-FV and PZN-YL, , as well as SARS-CoV-2 inhibitor PZ-WW, we next sought to investigate the protease inhibitory activities of isolated compounds.…”
Section: Resultsmentioning
confidence: 77%
“…In order to demonstrate the potential of our library, we conducted a proof-of-principle study by screening the mixture for potential QS inhibitors. This was based on our assay of natural products and previous research indicating that N-heterocycles, such as cyclic dipeptides or pyrrolones, can inhibit QS. Next, we aimed to extend this screening to the chemical library generated by CARs (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Curiously, a strain of R. aquimaris capable of interfering with QS systems through the production of a diketopiperazine has been reported [ 75 ]. Recently, it has also been described that synthetic diketopiperazines modified from the natural compound that is present in this species is capable of interfering with QS-related phenotypes in P. aeruginosa [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they also reported that fungi, Alternaria alternate derived Cyclo(Pro-Tyr), have the potential to inhibit the swarming motility of S. liquefaciens . The molecular docking studies showed that DKPs competitively bind to the receptor, CviR in C. violaceum or LasR receptor systems in P. aeruginosa PA01 (Holden et al, 1999 ; Sun et al, 2016 ; Wang et al, 2022 ). The analog binding changes the receptor's confirmation, which cannot bind to the target site.…”
Section: Discussionmentioning
confidence: 99%